2018
DOI: 10.1007/s11548-018-1852-1
|View full text |Cite
|
Sign up to set email alerts
|

Fully automatic segmentation of paraspinal muscles from 3D torso CT images via multi-scale iterative random forest classifications

Abstract: Our fully automatic, learning-based method can accurately segment paraspinal muscles from 3D torso CT images. It generates segmentation results that are better than those achieved by the state-of-the-art methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Xia and colleagues [11] tested several network architectures, including the U-Net as well as novel solutions, to segment psoas major, erector spinae, and multifidus, obtaining excellent Dice similarity scores between 0.913 and 0.95 for the best-performing neural network. Other studies achieved relatively lower performances [21], or focused on different imaging modalities or fields of view [22,23]. In general, it can be concluded that our model achieved state-of-the-art performance and is the only one that has been externally validated on a purposely created dataset so far.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Xia and colleagues [11] tested several network architectures, including the U-Net as well as novel solutions, to segment psoas major, erector spinae, and multifidus, obtaining excellent Dice similarity scores between 0.913 and 0.95 for the best-performing neural network. Other studies achieved relatively lower performances [21], or focused on different imaging modalities or fields of view [22,23]. In general, it can be concluded that our model achieved state-of-the-art performance and is the only one that has been externally validated on a purposely created dataset so far.…”
Section: Discussionmentioning
confidence: 65%
“…In order to test the performance of the segmentation tool on an external dataset, axial MRI scans of the whole lumbar spine were prospectively collected for 22…”
Section: External Validationmentioning
confidence: 99%
“…In the same context, it is also expected that the diagnosis and classification of joint-specific soft tissue will be improved, owing to the development of deep learning algorithms advantageous for segmentation. Indeed, there are several recent studies that have completed segmentation at a high level [64,65]. In particular, Hashimoto et al and others segmented the psoas major muscle through a U-net-based CNN model, and the trained U-net-based CNN model showed an average of 86.6% intersection over union (IoU).…”
Section: Discussionmentioning
confidence: 99%
“…Segmentation performances of these CNN structures in different CT images were evaluated using DOCs and the Hausdorff Distance (HD). We defined the automatically segmented set of voxels as AS and the manually defined ground truth as GT [ 16 ]. The DOC quantified the match between two sets by normalising the size of their intersection over the mean of their sizes, defined as follows: where the operator |·| returns the number of voxels contained in a region.…”
Section: Methodsmentioning
confidence: 99%
“…Segmentation performances of these CNN structures in different CT images were evaluated using DOCs and the Hausdorff Distance (HD). We defined the automatically segmented set of voxels as AS and the manually defined ground truth as GT [16].…”
Section: Model Performance Evaluation and Statistical Analysismentioning
confidence: 99%